HEALTH CENTERS ARE ON THE WAY TO RESTORE THE HEALTH OF THE POPULATION - DARIPOV SHAHOBIDDIN ISROILJONOVICH (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Today, the names "New Uzbekistan" and "New Stage of Uzbekistan's Development" are becoming very important in the chain of our relations in the international arena. In order to see the new Uzbekistan as a state with a new democratic image, which has completely changed the political, social and economic relations in the life of our society, it is the need of the hour to develop the healthcare system as well as all other sectors. All opportunities are being created for further development of this field. This article describes sanatoriums and their activities, created to improve the health of the population in all regions of our country.